MiRNA160 is associated with local defense and systemic acquired resistance against Phytophthora infestans infection in potato - Natarajan, Bhavani; Kalsi, Harpreet S.; Godbole, Prajakta; Malankar, Nilam; Thiagarayaselvam, Aarthy; Siddappa, Sundaresha; Thulasiram, Hirekodathakallu V.; Chakrabarti, Swarup K.; Banerjee, Anjan K. (Journal of Experimental Botany, 2018)
To combat pathogen infection, plants employ local defenses in infected sites and elicit systemic acquired resistance (SAR) in distant tissues. MicroRNAs have been shown to play a significant role in local defense, but their association with SAR is unknown. In addition, no such studies of the interaction between potato and Phytophthora infestans have been reported. We investigated the role of miR160 in local and SAR responses to P. infestans infection in potato. Expression analysis revealed induced levels of miR160 in both local and systemic leaves of infected wild-type plants. miR160 overexpression and knockdown plants exhibited increased susceptibility to infection, suggesting that miR160 levels equivalent to those of wild-type plants may be necessary for mounting local defense responses. Additionally, miR160 knockdown lines failed to elicit SAR, and grafting assays indicated that miR160 is required in both local and systemic leaves to trigger SAR. Consistently, SAR-associated signals and genes were dysregulated in miR160 knockdown lines. Furthermore, analysis of the expression of defense and auxin pathway genes and direct regulation of StGH3.6, a mediator of salicylic acid-auxin cross-talk, by the miR160 target StARF10 revealed the involvement of miR160 in antagonistic cross-talk between salicylic acid-mediated defense and auxin-mediated growth pathways. Overall, our study demonstrates that miR160 plays a crucial role in local defense and SAR responses during the interaction between potato and P. infestans.
Keywords: Auxin-salicylic acid antagonism; microRNA; miR160; Phytophthora infestans; Solanum chacoense; Solanum tuberosum; systemic acquired resistance

Comprehensive analysis of physiological and metabolomic responses to drought reveals specific modulation of acquired tolerance mechanisms in rice - Doddaraju, Pushpa; Dharmappa, Prathibha M.; Thiagarayaselvam, Aarthy; Vijayaraghavareddy, Preethi; Bheemanahalli, Raju; Basavaraddi, Priyanka A.; Malagondanahalli, Mohan Kumar V.; Kambalimath, Sumanth; Thulasiram, Hirekodathakallu V.; Sreeman, Sheshshayee M. (Physiologia Plantarum, 2023)
Mild stresses induce ``acquired tolerance traits'' (ATTs) that provide tolerance when stress becomes severe. Here, we identified the genetic variability in ATTs among a panel of rice germplasm accessions and demonstrated their relevance in protecting growth and productivity under water-limited conditions. Diverse approaches, including physiological screens, association mapping and metabolomics, were adopted and revealed 43 significant marker-trait associations. Nontargeted metabolomic profiling of contrasting genotypes revealed 26 ``tolerance-related-induced'' primary and secondary metabolites in the tolerant genotypes (AC-39000 and AC-39020) compared to the susceptible one (BPT-5204) under water-limited condition. Metabolites that help maintain cellular functions, especially Calvin cycle processes, significantly accumulated more in tolerant genotypes, which resulted in superior photosynthetic capacity and hence water use efficiency. Upregulation of the glutathione cycle intermediates explains the ROS homeostasis among the tolerant genotypes, maintaining spikelet fertility, and grain yield under stress. Bioinformatic dissection of a major effect quantitative trait locus on chromosome 8 revealed genes controlling metabolic pathways leading to the production of osmolites and antioxidants, such as GABA and raffinose. The study also led to the identification of specific trait donor genotypes that can be effectively used in translational crop improvement activities.